Cocoa, Blood Pressure, and Vascular Function - Ludovici, Valeria; Barthelmes, Jens; Nägele, Matthias P.; Enseleit, Frank; Ferri, Claudio; Flammer, Andreas J.; Ruschitzka, Frank; Sudano, Isabella (Frontiers in Nutrition, 2017)
Cardiovascular disease represents the most common cause of death worldwide. The consumption of natural polyphenol-rich foods, and cocoa in particular, has been related to a reduced risk of cardiovascular disease, including coronary heart disease and stroke. Intervention studies strongly suggest that cocoa exerts a beneficial impact on cardiovascular health, through the reduction of blood pressure, improvement of vascular function, modulation of lipid and glucose metabolism, and the reduction of platelet aggregation. These potentially beneficial effects have been shown in healthy subjects as well as in patients with risk factors (arterial hypertension, diabetes, and smoking) or established cardiovascular disease (coronary heart disease or heart failure). Several potential mechanisms are supposed to be responsible for the positive effect of cocoa; among them activation of nitric oxide synthase, increased bioavailability of nitric oxide as well as antioxidant, and anti-inflammatory properties. It is the aim of this review to summarize the findings of cocoa and chocolate on blood pressure and vascular function.